Mixed convection boundary layer flow of viscoelastic nanofluid past a horizontal circular cylinder: Case of constant heat flux - Rahimah, Mahat; Noraihan Afiqah, Rawi; Abdul Rahman, Mohd Kasim; Sharidan, Shafie (IOP Publishing, 2017)
The steady of two-dimensional convection boundary layer flow of a viscoelastic nanofluid over a circular cylinder is investigated in this paper. Carboxymethyl cellulose solution (CMC) is chosen as the base fluid and copper as a nanoparticle with the Prandtl number Pr = 6.2. The governing boundary layer partial differential equations are transformed into dimensionless forms. Then they are solved numerically by using the Keller-Box method. This paper focus on the effects of selected parameter on the flow and heat transfer characteristics and be presented in graphs. The results show that, the velocity profiles and the temperature profiles are increased by increasing the values of nanoparticles volume fraction. While velocity profile decreases when viscoelastic parameter is increase. The reverse trend is observed for the temperature profiles. Also, the values of reduced skin friction are increased by increasing mixed convection parameter, but the values of heat transfer coefficient produce an opposite behaviour with an increasing in mixed convection parameter.